IMPLEMENTASI KEBIJAKAN RETRIBUSI IZIN MENDIRIKAN BANGUNAN (IMB) DI KOTA MAGELANG BERDASARKAN PERATURAN DAERAH NOMOR 19 TAHUN 2011 - Maria Kurnia Sari; Sundarso Sundarso (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2017)
The policy of retributon for license building has been poured on regulation number 19 year 2011 about retribution for anyother license. This regulation are for increase the public license service, in particular for development. In addition, this regulation head for make supervision and control the buliding in the Magelang City and for increase the income of city. Altough there are regulation that regulate the retribution for license building in Magelang City. But in fact the regulation still not effective.This research aims at finding out how the implementation of the regulation abaiut retribution for license buliding in Magelang City and also to finding out the stimulation’s factors and the block’s factors. The methods that use in this resaerch is desciprtive-qualitative methode. In this research the writer use the five of regulatin exactness from Riant Nugroho to finding out the effectivisme of the implementation of regulation and implementation’s theory form Van Horn an Van Metter which influence the implementation of regulation. The result showed that the policy of retribution for license buliding in Magelang City still not maximal in the implementation. That proved by form total of the building in Magelang 35.312 just 22.55% that have the license buliding. It caused by the comunication beetwen public and government still less in order to make the license bulidng. The limit of human resource be a blocked this implementation and the social area that didn’t support the regulation. Therefor we need to increase the quality of human resource, the comunication beetwen public and government and repair the sosial area.